Let's go to the fair - Valvassori;Maureen (New Delhi Sterling Publishers Pvt Ltd, 2000)
Embark on a fun and frolic filled journey with Barney, the friendly dinosaur and his friends, B.J. and Baby Bop through these simple and interesting stories, activity and colouring Books. Learn, Read and Smile.